A new scanning method for fast atomic force microscopy - Mahmood, Iskandar Al-Thani; Moheimani, S.O. Reza; Bhikkaji, Bharath (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
In recent years, the atomic force microscope (AFM) has become an important tool in nanotechnology research. It was first conceived to generate 3-D images of conducting as well as nonconducting surfaces with a high degree of accuracy. Presently, it is also being used in applications that involve manipulation of material surfaces at a nanoscale. In this paper, we describe a new scanning method for fast atomic force microscopy. In this technique, the sample is scanned in a spiral pattern instead of the well-established raster pattern. A constant angular velocity spiral scan can be produced by applying single frequency cosine and sine signals with slowly varying amplitudes to the x-axis and y -axis of AFM nanopositioner, respectively. The use of single-frequency input signals allows the scanner to move at high speeds without exciting the mechanical resonance of the device. Alternatively, the frequency of the sinusoidal set points can be varied to maintain a constant linear velocity (CLV) while a spiral trajectory is being traced. Thus, producing a CLV spiral. These scan methods can be incorporated into most modern AFMs with minimal effort since they can be implemented in software using the existing hardware. Experimental results obtained by implementing the method on a commercial AFM indicate that high-quality images can be generated at scan frequencies well beyond the raster scans.